Foreign Tourist Preferences for Sanur Bali Tourism Destination Components - Rizky Efrido Aryada; Anom Hery Suasapha; Dewa Made Ayu Lily Dianasari (Indonesian Journal of Interdisciplinary Research in Science and Technology, 2025)
Preference is a process carried out by consumers when they are going to buy goods and services. The purpose of this study was to determine the preferences of foreign tourists towards tourism components in the Sanur Tourist Destination. The sample used in this study was 200 foreign tourists. The attributes of tourism components used in this study were avilliable packages, attractions, activities, prices, ancillary, amenities and accibilities. The results of this study are that foreign tourists' preferences for tourism components in the Sanur Tourist Destination prefer tourism components in the Sanur tourist destination that have components of artificial tourism types compared to other types of tourist attractions. However, when talking about accessibility, foreign tourists tend to choose components of easy-to-reach access, but when it comes to amenity factors, foreign tourists' preferences will choose tourist destinations that have complete amenities with various tourist activities. Foreign tourists' preferences tend to choose components of tourist destinations that have prices that tend to be cheap and there is management of tourists visiting Sanur.